HUBUNGAN INFLASI DENGAN PENJUALAN SUKUK RITEL SEKTOR KEUANGAN SYARIAH PERIODE 2018-2022 - Rimayanti; wanda, putri wanda (Jurnal Ilmiah Ekonomi Bisnis, 2024)
The purpose of this study was to test whether there is a correlation between the inflation rate and yield with the sale of retail sukuk in the Islamic financial sector in the 2018-2022 period. This research is a type of documentation research with an associative quantitative approach. Data was collected through official websites and literature studies. Sampling using saturated sample technique, using the entire population consisting of 24 samples in retail sukuk sales. This study shows that there is a significant relationship between inflation and retail sukuk sales at 0.000 â‰¤ 0.05 significance, with a very strong correlation coefficient of 1.000**, and the direction of the relationship shows perfect positive. Similarly, there is a significant relationship between yield and retail sukuk sales at 0.000 â‰¤ 0.05 significance, with a very strong correlation coefficient of 0.994**, and the direction of the relationship is positive.